Agama dalam Negara antara Teokrasi, Sekuler, dan Tamyiz - Mohamad Arief Khumaidi (UIN Sunan Gunung Djati Bandung, 2021)
Ahmad Sadzali in his book describes the relationship between religion and the state, which according to him is a conversation that has been going on for a long time and continues, including in Indonesia. This book is divided into three chapters, explaining theocracy, secularism, and tamyiz. Tamyiz is a thought that bridges the two extreme opinions between theocracy and secularism, which is a form of the middle way of thinking. This book does not look at what is no less important than the theme of the relationship between religion and the state, which is related to citizen participation in political decision-making. Often in a secular state, ignoring the opinions of religious people is considered inconsistent with the principles of state neutrality, as stated by John Rawls, especially in the theory of public reason.